Guia de procedimentos para o tratamento de erros de divulgação do Inep - Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2024)
In this document, the National Institute of Educational Studies and Research Anísio Teixeira (Inep) presents its procedures for dealing with disclosure errors. The typology of errors and the Institute's reaction to each type of error detected are considered, considering the different forms of disclosure adopted by Inep. This guide is in line with the Fundamental Principles of Official Statistics, established by the United Nations Statistical Commission (UN, 2014) and adopted by Inep (Brazil. Inep, 2017). With this, Inep reaffirms its institutional mission of “producing scientific knowledge and official information to improve public educational policies, contributing to the social and economic development of the country” (Brazil. Inep, 2020, p. 12).